Carbon footprints and social carbon cost assessments in a perennial energy crop system: A comparison of fertilizer management practices in a Mediterranean area. (January 2021) - Solinas, Stefania; Tiloca, Maria Teresa; Deligios, Paola A.; Cossu, Marco; Ledda, Luigi
Abstract: Agriculture is strongly linked to climate change and has a two-sided relationship with climate change. Although climate change contributes to reducing agricultural productivity, the primary sector is responsible for the production of greenhouse gas (GHG) emissions; on the other hand, the primary sector could mitigate emissions to foster soil carbon sequestration. Specifically, perennial energy crop systems could produce relevant environmental and socio-economic benefits. This study aimed to highlight the potential efficacy of various fertilizer management strategies in reducing GHG emissions and increasing the social value obtained from carbon storage. Using two methodological approaches, namely, the carbon footprint (CF) and social carbon cost (SCC) methods, five nitrogen fertilization patterns (low input, LI; high input, HI; LI + biochar, LI + Bi; LI + cover crop, LI + CC; and LI + Bi + CC) were compared in an experiment on cardoon cultivation for three consecutive growing seasons. GHG release exceeded GHG removal and ranged from 0.20 (HI) to 0.14 (LI + CC) t CO2 e per production unit. LI + CC reduced GHG emissions and optimized yield. The rates of carbon sequestration ranged from 72.7 (HI) to 26.2 (LI) t CO2 e t −1 of biomass. Furthermore, the combined use of biochar and a cover crop had no positive effects on C sequestration or GHG emission reduction, unlike these treatments individually. In fact, LI + Bi provided the highest value for C storage (61.1 t CO2e t − 1 of biomass), and LI + CC had the best GHG balance (0.14 t CO2 e per production unit). The monetary evaluation of C storage showed that HI would produce the greatest benefits until 2050 (i.e., 9 K US dollars per t CO2 e). Although a single best option was not identified among the fertilizer management practices, identifying the optimal trade-offs among productivity, GHG emissions reduction and SCC value is important in ensuring that an energy crop will provide food security as well as environmental and socio-economic sustainability. Furthermore, a potential optimal solution could allow improvements in long-term crop system planning and land use and the development of effective strategies to combat climate change. Highlights: Five nitrogen fertilizations were compared in a long term experiment on cardoon. Carbon footprint and monetary carbon value of cardoon were assessed in the long term. Cover crop contributed to reduce greenhouse gas emissions provided by cardoon. Combining biochar and cover crop was worse than biochar use in terms of carbon stock. The use of high nitrogen rate fostered social cost related to soil carbon stock.